Recent advances in novel tumor immunotherapy strategies based on regulating the tumor microenvironment and immune checkpoints - Jing, Hanhui; Gao, Yan; Sun, Zongsheng; Liu, Shanglong (Frontiers in Immunology, 2025)
Tumor immunotherapy, a novel and rapidly progressing cancer treatment, has experienced remarkable advancements over recent years. It focuses on augmenting the patient’s immune defenses and remodeling the immune microenvironment (IME) of tumors, rather than directly targeting malignant cells. The efficacy of immunotherapy relies substantially on multiple components within the tumor microenvironment (TME), extending beyond adaptive immunity alone. Immune cells within the TME play critical roles in both promoting immune surveillance and facilitating immune evasion. This complexity emphasizes the importance of immune checkpoint regulation in immunotherapeutic interventions. Therapeutically targeting specific immune cell subsets and metabolic pathways in combination treatments can transform an immunosuppressive TME into one that is immunologically activated, facilitating enhanced immune cell infiltration and consequently improving immunotherapy efficacy. Nevertheless, comprehensive research remains necessary to fully elucidate the mechanisms underlying TME interactions and immune checkpoint regulation, ultimately enabling more effective immunotherapeutic approaches.